Critical thinking, literature and teachers' instructional activities: An Indonesian case of community service program for English teachers - Isti Gandana; Nia Nafisah; Ernie Imperiani (English Language Teaching Educational Journal, 2021)
Critical thinking (CT) has generally been known as one of the core competencies of the 21st-century skills that students need to acquire to succeed in today’s world. To attain this goal, teachers undoubtedly have a critical role to play. Involving a group of Indonesian teachers of English, this study aims to explore the teachers’ initial conceptions of critical thinking as reflected in their planned classroom activities. Specifically, the data collected were in the form of written instructional activities that  used literary works as learning materials. These data were obtained following the teachers’ participation in an online workshop on promoting critical thinking through literature  held for English teachers from MGMP (i.e., English Teachers Working Group) in Bandung Regency. The workshop introduced a model of teaching critical thinking skills using literary works  and required the teachers to design their own instructional activities based on the proposed CT model. Adopting content analysis as the methodological tool to scrutinize the teachers’ prepared materials,  our initial findings indicate that, in general, the teachers had inadequate knowledge of how to incorporate  critical thinking skills into their teaching. Literature was seen merely as a tool to develop students’ linguistic abilities rather than as a way to explore humans’ experiences and to connect ‘the word and the world’. This study recommends that the teachers be given more time to better explore the concepts surrounding  critical literacy  pedagogy  as well as be given more opportunities  for practical application of the promoted instructional model.